(untitled) (Stato, Chiese e pluralismo confessionale, 2013)
contributo sottoposto a valutazione SOMMARIO: 1. Ineliminabile interesse del diritto canonico nella riflessione ius-religiosa del post-moderno - 2. L’ermeneutica del rinnovamento nella continuità e la metodologia suggerita dal Concilio Vaticano II: pregi e difetti di una transizione permanente - 3. La richiesta di riconsiderazione delle istanze poste dall’umana coscienza - 4. Una proposta alternativa rispetto a canoni e confini delle (presunte) leggi di mercato - 5. Prime conclusioni: verso un approccio assiologico e razionale sull’analisi degli istituti. ABSTRACT The fundamental reasons of Canon Law to be considered as theoretical contribution to the secular juridical science The aim of this article is to underline how secular Law surprisingly shows a great influence on Canon Law’s theories and how doctrines and disciplines introjected from ecclesiastical Orders have moulded and modified civil institutions. The most controversial points, in the last decade, still seem the interpretation and the application of the Second Vatican Council, properly because many scholars are daily arguing about inner aftermath of the event, if in consistent behaviour, or in an unpredicted disagreement, with Roman Catholic Church and generally Christianity’s history. Anyhow, current debates, concerning the crisis of liberal politics and the decline of a meaningful conception of sovereignty, should be cleared up by considering how controversies about jurisdiction, power and its legitimacy were composed during the past. PAROLE CHIAVE Ordinamento Canonico; Concilio Vaticano II; Fonti del Diritto; Secolarizzazione. KEY-WORDS Canon Law; Second Vatican Council; Sources of Law; Secularization.